2019
DOI: 10.14214/sf.10217
|View full text |Cite
|
Sign up to set email alerts
|

Developing growth models for tree plantations using inadequate data – a case for Korean pine in Northeast China

Abstract: Pinus koraiensis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…plantations in Heilongjiang Province were 79.7, 16.6 and 16.2 million m 3 , respectively, accounting for 33.6%, 53.6% and 61.3% of the national growing stock of these species in plantations. These conifers are the main species in northeast China in terms of economic return, timber supply and cone production (Jin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plantations in Heilongjiang Province were 79.7, 16.6 and 16.2 million m 3 , respectively, accounting for 33.6%, 53.6% and 61.3% of the national growing stock of these species in plantations. These conifers are the main species in northeast China in terms of economic return, timber supply and cone production (Jin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of L. olgensis, Pinus sylvestris and Pinus koraiensis in China, few diameter distribution models representing all the Heilongjiang region are available for forest management and planning. Model development has been hindered because permanent plots and silvicultural experiments were not designed for modelling purposes (Jin et al 2019). Published models are often targeted to small geographic areas, specific species and stand structures, thus limiting their wider applicability.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with irregular measurement intervals in this research, an optimization approach originally suggested by and later used by de-Miguel et al (2014), Juma et al (2014) andJin et al (2019) among others, was used to fit the diameter increment and survival models. This method seems to overcome some of the problems related to other methods and has been shown to produce similar models and model parameters to regression analysis .…”
Section: Introductionmentioning
confidence: 99%